A Model of Memory Linking Time to Space - Löffler, Hubert; Gupta, Daya Shankar (Frontiers in Computational Neuroscience, 2020)
The storage of temporally precise spike patterns can be realized by a single neuron. A spiking neural network (SNN) model is utilized to demonstrate the ability to precisely recall a spike pattern after presenting a single input. We show by using simu-lation that the temporal properties of input patterns can be transformed into spatial patterns of local dendritic spikes. The localization of time-points of spikes is facilitated by phase-shift of the subthreshold membrane potential oscillations (SMO) in the dendritic branches, which modifies their excitability. In ref-erence to the points in time of the arriving input, dendritic spikes are triggered in different branches. To store the spatially distributed pattern, two unsupervised learning mechanisms are utilized. Either synaptic weights to the branches, spatial repre-sentation of the temporal input pattern, are enhanced by spike-timing-dependent plasticity (STDP) or the oscillation power of SMOs in spiking branches is increased by dendritic spikes. For retrieval, spike bursts activate stored spatiotemporal patterns in dendritic branches, which reactivate the original somatic spike patterns. Plausibility, advantages, and some variations of the proposed model are also discussed.